A Shoot-Specific Hypoxic Response of Arabidopsis Sheds Light on the Role of the Phosphate-Responsive Transcription Factor PHOSPHATE STARVATION RESPONSE1. Issue 2 (21st April 2014) - Klecker, Maria; Gasch, Philipp; Peisker, Helga; Dörmann, Peter; Schlicke, Hagen; Grimm, Bernhard; Mustroph, Angelika
Abstract : Oxygen and phosphate deficiency trigger overlapping changes in gene expression, including genes for galactolipid metabolism, which are mediated by a common transcription factor. Abstract: Plant responses to biotic and abiotic stresses are often very specific, but signal transduction pathways can partially or completely overlap. Here, we demonstrate that in Arabidopsis ( Arabidopsis thaliana ), the transcriptional responses to phosphate starvation and oxygen deficiency stress comprise a set of commonly induced genes. While the phosphate deficiency response is systemic, under oxygen deficiency, most of the commonly induced genes are found only in illuminated shoots. This jointly induced response to the two stresses is under control of the transcription factor PHOSPHATE STARVATION RESPONSE1 (PHR1), but not of the oxygen-sensing N-end rule pathway, and includes genes encoding proteins for the synthesis of galactolipids, which replace phospholipids in plant membranes under phosphate starvation. Despite the induction of galactolipid synthesis genes, total galactolipid content and plant survival are not severely affected by the up-regulation of galactolipid gene expression in illuminated leaves during hypoxia. However, changes in galactolipid molecular species composition point to an adaptation of lipid fluxes through the endoplasmic reticulum and chloroplast pathways during hypoxia. PHR1-mediated signaling of phosphate deprivation was also light dependent. Because a photoreceptor-mediated PHR1 activation was not detectable under hypoxia, our data suggest that a chloroplast-derived retrograde signal, potentially arising from metabolic changes, regulates PHR1 activity under both oxygen and phosphate deficiency.